2012
DOI: 10.3109/09513590.2012.664191
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the lipid profile in post menopausal women who use estradiol and testosterone implants

Abstract: The use of E and T implants showed some statistically significant decrease in TC at the beginning of the HT and some decrease in LDL in the group using HT. In the group without HT there was no difference in lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Several studies in post-menopausal women have also reported an inverse relation between endogenous androgen levels, dyslipidemia and atherosclerosis (Bernini et al, 2001;Khatibi et al, 2007;Ouyang et al, 2009). Furthermore, improvements in lipid profiles following estradiol/testosterone replacement therapy have been reported in post-menopausal women (Castelo-Branco et al, 2007;Britto et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies in post-menopausal women have also reported an inverse relation between endogenous androgen levels, dyslipidemia and atherosclerosis (Bernini et al, 2001;Khatibi et al, 2007;Ouyang et al, 2009). Furthermore, improvements in lipid profiles following estradiol/testosterone replacement therapy have been reported in post-menopausal women (Castelo-Branco et al, 2007;Britto et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…The studies carried out in postmenopausal women have reported an inverse relation between estrogen levels, dyslipidemia, and atherosclerosis (21,22). The improvements in lipid profile following hormonal replacement therapy have been established in postmenopausal women (23). Lipid status was evaluated among the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Higher doses of T have been shown to correlate with a more significant improvement in quality of life. In addition, previous studies have not confirmed side effects such as deepening of the voice [81] and worsening of cholesterol [82]. There is an improvement in symptoms with T implants as evidenced by the 'Menopause Rating Scale' total score, including symptom reduction and improvement in psychological and urogenital complaints [1].…”
Section: The Benefits and Effectiveness Of T Implant Therapymentioning
confidence: 92%